INTERAKSI SOSIAL EKONOMI MASYARAKAT TERHADAP KAWASAN TAMAN NASIONAL BUKIT TIGA PULUH (STUDI KASUS DESA RANTAU LANGSAT KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU PROVINSI RIAU) - Melyana, Meriza; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Forest have a variety of functions for human life, either directly function in supporting the socio-economic life of everyday people, as well as indirect. Interaction between humans and forest occured a very long time in various National Park, this research has been conducted in the village of Rantau Langsat Sub-District of Batang Gansal Indragiri Hulu District Riau Province. This study was conducted in January-February 2015. The results of this study indicate that the socio-economic characteristics based on; age are productive working age of 22-65 years that is equal to 29.41%, the level of education is largely elementary school and that is equal to 94.11%, the majority of farmers have a number of family members 6 at 29.41%, revenues between Rp.250,000 to Rp. 750,000 amounted to 41.18%, community livelihood as rubber farmers are 88,23% and as much as 91,17% of the people have  land. Forms of interaction that occurred between community with the Bukit Tiga Puluh National Park is a ectractive pattern.  Keywords : Interaction, Forest Community, Utilization, Forest Product